The degree to which Arabic language teachers possess the skill of building cognitive objectives in the Giza District Education Directorate from the point of view of principals - Abualkheil, Majed Salem Abdul Kareem (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the degree to which Arabic Language teachers possess the skill of building cognitive objectives in the Giza District education directorate from the point of view of principals. To achieve the objectives of the study, the researcher used the descriptive survey method, and a questionnaire consisting of (23) items divided into three areas, which were distributed to a random sample consisting of (70) female and male principals.The result of SPSS analysis shown that The degree to which Arabic Language teachers possess the skill of building cognitive objectives in the Giza District education directorate from the point of view of principal was High with average (3.71 out of 5), The finding also showed there is no statistically significant differences at (α≤0.05) refers to principal sex (male and female) in addition there were statistically significant differences refers to principal years of experience in favor of (10 years and more). The study recommends a set of recommendations, the most important of which are diversification in supervisory practices, and the development of training programs to enrich the theoretical background of teachers regarding the skill of formulating behavioral goals.
Keywords: skill; cognitive objectives; Arabic language teachers; school principals; Giza District